2013
DOI: 10.1002/wrcr.20372
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying groundwater-surface water interactions in a proglacial moraine using heat and solute tracers

Abstract: [1] Recent studies in mountain environments have indicated that groundwater represents a major component of the water balance of alpine streams and lakes. However, the scarcity of information on the hydraulic properties of geological materials in alpine environments presents a major obstacle to understanding the response of these watersheds to hydrological inputs and their future variability. The information is particularly limited for talus and proglacial moraine, where rugged topography prohibits the install… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
39
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 53 publications
(101 reference statements)
7
39
0
Order By: Relevance
“…Conversely, the use of tracers can be helpful in discriminating different contributions (Anderson, 2005;Langston et al, 2013). Conversely, heat can be used efficiently to determine groundwater seepage across streambeds (Schmidt et al, 2007;Constantz, 2008) and at the bottom of lakes (Langston et al, 2013). Artificial tracers can usually be used for short periods (Anderson, 2005) in remote and harsh environments.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the use of tracers can be helpful in discriminating different contributions (Anderson, 2005;Langston et al, 2013). Conversely, heat can be used efficiently to determine groundwater seepage across streambeds (Schmidt et al, 2007;Constantz, 2008) and at the bottom of lakes (Langston et al, 2013). Artificial tracers can usually be used for short periods (Anderson, 2005) in remote and harsh environments.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is very difficult to quantify available groundwater resources, it is estimated that there is more groundwater in Canadian aquifers than surface water in rivers and lakes, similar to what is observed elsewhere (Rivera 2014). In the generally humid and cold Canadian climate, groundwater-surface water interactions are omnipresent (Devito et al 1996;Langston et al 2013;Brannen et al 2015;Foster and Allen 2015), but remain relatively seldom studied. The Canadian Council of Academies (CCA 2009, 185) expert panel on groundwater concluded that a sustainable use of groundwater resources requires that "groundwater and surface water be characterised and managed as an integrated system within the context of the hydrological cycle in a watershed or groundwatershed."…”
Section: Preface To the Special Issuementioning
confidence: 99%
“…Permanent lakes usually interact with the surrounding groundwater (GW) system in three main ways [21]: some receive GW inflows, some have seepage loss to the GW, and others receive from and lose to the GW system [9]. There are various methods of quantifying the lake water-groundwater interaction: the measurement of seepage using flownet or seepage meters [22][23][24], simulation (mathematical) models based on Darcy's law [25][26][27], the heat tracer method [23,28,29], the water budget method [30][31][32], the chemical/solute mass balance method [32][33][34][35], or the use of stable isotopes [26,36]. Detailed reviews of the different GW flux estimation methods are well documented [22,23,26,36].…”
Section: Introductionmentioning
confidence: 99%